THE EFFECT OF EMPLOYEE RELATIONS PRACTICES ON EXECUTIVES' PERFORMANCE IN MANUFACTURING FIRMS AT KULIM HI-TECH PARK, KULIM, KEDAH, MALAYSIA - Bokhori Md Amin, (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
The purpose of this study is to assess the extent of the role of employee relations and their contribution to the performance of executives in manufacturing firms. Methodology in this study was built where a questionnaire was designed for data collection to measure employee relations-related communication sessions, employee representative committee, harmonious atmosphere, providing fair treatment and counseling to improve satisfaction on executives' performance. Data were collected among executives in manufacturing firms at Kulim Hi-tech Park, Kulim, Kedah, Malaysia. A stratified sampling method was used to collect data and the data obtained were analyzed using SmartPls 3.7.8. The finding of this study found that there is a significant relationship between communication sessions, employee representative committee, harmonious atmosphere, fair treatment, and counseling sessions to improve satisfaction on executives' performance. It is proved from SmartPls analysis shown that all independent variables have a positive impact on executives' performance in manufacturing firms. The limitation of the study only covers the manufacturing firms. Another limitation is the respondents only included executives. Apart from these limitations, this study can give a strong impact on the top management of manufacturing firms to design the strategy of employee relations to be more effective in improving the work performance of executives.